Development of Evaluative-Process Learning Tools Integrated with Conceptual-Problem-Based Learning Models: Study of Its Validity and Effectiveness to Train Critical Thinking - Herdiyana Fitriani; Taufik Samsuri; Fida Rachmadiarti; Raharjo Raharjo; Christabel Dudu Mantlana (International Journal of Essential Competencies in Education, 2022)
This study aimed to develop an evaluative-process learning tool integrated with the conceptual-problem-based learning (CPBL) model to train students' critical thinking skills. The learning tools developed (lesson plans, textbooks, worksheets, and critical thinking test instruments) were evaluated for validity and Effectiveness in training students' critical thinking skills at the higher education level. Validity evaluation is carried out on content and construct validity aspects. This is done through a focus group discussion (FGD) mechanism involving four expert validators. Furthermore, the Effectiveness of the developed learning tools is evaluated by implementing them in the classroom. The experimental design (intact-group comparison) involved a sample group from the State Islamic University of Mataram. The experimental group was taught by evaluative-process learning tools integrated with the CPBL model, while lectures and discussions taught the control group. Critical thinking data were collected using a valid essay test instrument, and the results were analyzed. The validity test results show that all the elements that make up the learning tools in the aspect of content and construct validity have been declared valid. Furthermore, at the implementation stage in the classroom, evaluative-process learning tools integrated with the CPBL model have been effective in training students' critical thinking skills compared to teaching that relies on lectures and discussion. This Effectiveness is based on two aspects, (1) the conceptual framework of the CPBL model, which is constructed and arranged from a problem-based learning model with five learning steps, namely prior knowledge, organize, investigate, analyze, and evaluation; (2) the concept of evaluative-process which is integrated with the CPBL model. These two aspects support capacity in training students to think critically.